Bamboo-fiber-reinforced thermoset and thermoplastic polymer composites: a review of properties, fabrication, and potential applications - Radzi, A. M.; Zaki, Sheikh; Hassan, Mohamad Zaki; Ilyas, R. A.; Jamaludin, Khairur Rijal; Md Daud, Mohd Yusof; Abdul Aziz, Sa’ardin (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Natural-fiber-reinforced composites, especially bamboo, are an alternative material to compete with conventional materials. Their environmentally friendly, renewable, low-cost, low-density, non-toxic, and fully biodegradable properties are concerning for researchers because of their advantages over synthetic polymers. This comprehensive review presents the results of work on bamboo fiber composites with special reference to bamboo types, thermoplastic and thermoset polymers matrices, hybrid composites, and their applications. In addition, several studies prove that these properties are very good and efficient in various applications. However, in the development of composite technology, bamboo fiber has certain constraints, especially in moisture conditions. Moisture is one of the factors that reduces the potential of bamboo fiber and makes it a critical issue in the manufacturing industry. Therefore, various efforts have been made to ensure that these properties are not affected by moisture by treating the surface fibers using chemical treatments.